Public’s perception and attitude towards Singapore’s charity incidents and the impacts on donation intention. - Wee, Min Yu. (2012)
This research study seeks to gain a better understanding of the local charity scene in the aftermath of the local charity incidents which occurred in 2005 and 2007. The objective of our research is to understand the perspectives of youths in Singapore and whether the incidents have affected their donation behaviour. For this study, we adopted a revised Theory of Planned Behaviour (TPB) model to determine the influence of Attitude towards the Charity Incidents, Attitude towards behaviour, Perceived Control of Consequences, Descriptive Norm, Injunctive Norm, Moral Norm, Perceived Behavioural Control and Past Behaviour on Behavioural Intentions i.e. intentions to contribute monetary donations to charitable organisations. Respondents were made up of past donors aged between 20 and 30, and they completed a full online questionnaire comprising of 46 questions to assess the various constructs of the revised TPB model.